Diabetes mellitus with anti-glomerular basement membrane disease and anti-tubular basement membrane disease: a rare case report of reversible dialysis dependence - Hu, Junqi; Liang, Yuanzi; Sun, Kebing; Xiao, Yuefei (Frontiers in Immunology, 2026)
We present an instructive case of an elderly woman with a history of diabetes and diabetic retinopathy who was admitted due to rapidly progressive renal failure requiring dialysis. Although diabetic nephropathy was initially suspected, the patient’s rapid clinical decline, significant hematuria, and proteinuria inconsistent with typical diabetic nephropathy prompted further serological evaluation and renal biopsy. Pathological examination revealed the rare coexistence of anti-glomerular basement membrane disease and anti-tubular basement membrane-associated interstitial nephritis. Following aggressive immunosuppressive therapy and plasma exchange, the patient was successfully weaned off dialysis with marked improvement in renal function. This case highlights the importance of comprehensive assessment in diabetic patients with atypical renal presentations and underscores the critical role of renal biopsy in guiding treatment decisions.